The Representation of the Reportedspeech Through - Sulaimonovich, Safarov Firuz (European Journal of Life Safety and Stability (2660-9630), 2022)
The article undergoes component and text analysis of one of the varieties of communicative meaning, that is, indirect report. An attempt is being made to more fully disclose the features of noun-predicate based on micro texts taken from fiction.